Long term follow up of the EORTC 18952 trial of adjuvant therapy in resected stage IIB–III cutaneous melanoma patients comparing intermediate doses of interferon-alpha-2b (IFN) with observation: Ulceration of primary is key determinant for IFN-sensitivity. (March 2016) - Eggermont, Alexander M.M.; Suciu, Stefan; Rutkowski, Piotr; Kruit, Willem H.; Punt, Cornelis J.; Dummer, Reinhard; Salès, François; Keilholz, Ulrich; de Schaetzen, Gaetan; Testori, Alessandro; ,
Abstract: Background: We report on the long term outcome of the EORTC 18952 adjuvant interferon (IFN) trial in 1388 resected stage IIB/III melanoma patients and identify key predictive factors for outcome. Methods: We analysed outcome of the EORTC 18952 trial (4 weeks of IFN, 10 MU, 5 times/week for 4 weeks followed by 12 months IFN at 10 MU, 3 times/week versus followed by 24 months IFN at 5 MU 3 times/week versus observation) regarding relapse-free survival (RFS), distant metastasis-free interval/survival (DMFI/DMFS), and overall survival (OS), and analysed potential predictive factors of outcome. Findings: At a median follow-up of 11 years, the comparison of IFN 13 months versus IFN 25 months versus observation yielded estimated hazard ratios (HR) for RFS of 0.94 versus 0.84 (p = 0.06); for DMFI 0.95 versus 0.82 (p = 0.027); for DMFS 0.95 versus 0.84 (p = 0.07); and for OS 0·95 versus 0.84 (p = 0.08), respectively. The impact of treatment was greatest in the ulceration group, whereas in patients with non-ulcerated primaries the impact was null (HR ≥ 1.0). In patients with ulcerated melanoma the HR for IFN 13 months versus 25 months versus observation were for: RFS 0.82 (p = 0.16) versus 0.61 (p = 0.0008); DMFS 0.76 (p = 0.06) versus 0.57 (p = 0.0003); OS 0.80 (p = 0.13) versus 0.59 (p = 0.0007). In stage IIB/III-N1 (microscopic nodal involvement only) patients with ulcerated melanoma the HR estimates were for: RFS 0.85 versus 0.62; DMFS 0.80 versus 0.56; OS 0.77 versus 0.54. Conclusions: This long term report of the EORTC 18952 trial demonstrates the superiority of the 25-month IFN schedule and defines ulceration of the primary as the overriding predictive factor for IFN-sensitivity. Highlights: The 25-month interferon (IFN) schedule yielded to better outcome than the observation group. Ulceration of the primary is a strong predictive factor for IFN-alpha sensitivity. Stage IIB–IIIN1 patients with an ulcerated primary had the highest treatment benefit.